Impact of Microfinance on Economic and Social Spending Patterns of User Groups- Evidence from Western Hill, Nepal - Silwal, Sudarshan (International Research Journal of MMC, 2024)
Microfinance refers to financial services such as loans, saving, insurance and other basis banking products. These services are typically offered by MFIs, aiming to empower and support low income and underserved communities who are often excluded from formal banking sector due to the factors like poverty, lack of collateral and limited credit history. This paper delves into the impact of microfinance services on user groups in the Western Hills of Nepal. This research work follows mixed methods approach. Thematic analysis and statistical software have been applied for the analysis of data obtained from the field study. The majority of microfinance users in the study are found female, married, engaged in agriculture, having primary education and using this service for several years mainly for expanding business. As per the answer of the respondents, MFIs cater to the poor and fulfill their needs, improvement in household income, and access to education, healthcare and women participation in economic actives. The study revealed that there is significant increase in monthly income, saving and bank balance, spending on education and small business after the involvement in microfinance service. Consumption and health spending found decreasing, and festival spending remained relatively unchanged after the involvement. High interest rate and loan repayment system found challenging in the study area. This study suggests that there is need to address these challenges to enhance its effectiveness further and ensure financial stability for the microfinance user groups of the study area.